ChemInform Abstract: Recent Advances in Iron Complexes as Potential Anticancer Agents. Issue 13 (March 2016) - Wani, Waseem A.; Baig, Umair; Shreaz, Sheikh; Shiekh, Rayees Ahmad; Iqbal, Prince Firdous; Jameel, Ehtesham; Ahmad, Akil; Mohd‐Setapar, Siti Hamidah; Mushtaque, Md.; Ting Hun, Lee
Abstract: Review: 199 refs.